Auditoría de riesgo en la cuenta efectivo y equivalente a efectivo de la Empresa Blanca-Rosa Export S.A. en el cantón Quinsaloma en el periodo 2022. - Crespo Carpio, Marcos Segundo (2023)
This case study focuses on a risk audit that presents the Cash and Cash Equivalent account in the company Blanca-Rosa Export S.A located in the province of Los Ríos in the Quinsaloma canton, which is dedicated to the commercialization and export of cocoa. A good control of the risk of the Cash and Cash Equivalent account since it allows to know how this account is managed by the company, the present project makes a risk audit in the Cash and Cash Equivalent account to see what risks the company does not have in mind, which are not in plain sight, thanks to this analysis the company will be able to correctly know what the risks are, what this account is going through and how to minimize these same risks, this will benefit the company in the way it that the Cash and Cash Equivalent account is found and how it is managed, a quantitative approach was chosen because we reviewed accounting documents presented by the company and it will allow obtaining the results of the general and specific objectives and the questionnaire method was changed as a technique to know the level of risk presented by the Cash and Cash Equivalent account in the company Blanca-Rosa Export S.A.